THE PORTRAYAL OF WOMEN IN THE GREAT GATSBY BY F. SCOTT FITZGERALD AND IT’S RELATIONSHIP TO INDONESIAN WOMEN ON EDUCATION - Himawan Agung Rida Pambudi; Barnabas Sembiring; Indah Damayanti (Universitas Bengkulu, 2018)
This research is aimed to find out and explain the characteristics of women character, to know how the novel portrayed the women and how Indonesian women on education portrayed. According to the data, the researcher gets the result that show characteristics of 3 major women characters. Daisy Buchanan has two characteristics, there are Pessimistic and Materialistic, Jordan Baker also has two, Masculine and Worried, and the last is Myrtle Wilson is Materialistic. Besides that, the researcher also explains the portrayal of women in the novel and relate it to the 1920s era where does the novel come from. The researcher also compared and portrayed the characteristics of American women in the novel and Indonesian women characters.